Pengaruh Pemberian Reward dan Punishment terhadap Kinerja Karyawan pada PT. Rukun Mitra Sejati Jambi - Devita, Reni; Yandi, Andri; SM, Aprilia Kinanti (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to determine the effect of reward and performance punishment on employees at PT. Jambi True Partner Pillars.The types of data used in this study are primary data and secondary data which are descriptive and quantitative regarding Reward, Punishment and Employee Performance. the data in this study were obtained from PT. Jambi True Partner Pillars.The sample of this research is a company employee engaged in the distribution of food goods. By using the method of interviews, observation and questionnaires. All employees must meet the requirements as a research sample with a total of 42 employees. The analytical tool used in this study is multiple linear regression analysis.The results of this study indicate that: Reward has a significant effect on Employee Performance, Punishment has a significant effect on Employee Performance, Reward and Punishment have a significant effect on Employee Performance.Based on the research results, it can be concluded that performance reward and punishment for employees simultaneously have a significant effect where Fcountgreater than Ftable (34.765 > 3.24). And partially the reward (X1) is 0.299, where the value of tcount is greater than ttable (3.453 > 2.024). with a significance value of 0.001 <0.05. and Punishment (X2) of 0.559. Where the tcount value is greater than the table (6.062 > 2.024) with a significance value of 0.000 <0.05. And a constant of 2,174, the performance of employees at PT. The Rukun Mitra Sejati Jambi experienced an increase of 2,174. So, Reward and Punishment have a significant effect on Employee Performance.